Assessment of Cranial Sonographic Findings of Hypoxic Ischemic Brain Injury in Perinatal Asphyxia - Yasmin, Tarana; Akther, Shaheen; Sultana, Sohely; Amin, Mashah Binte (Journal of Medicine, 2016)
Background: In perinatal asphyxia, hypoxic ischemic brain injury remains most serious condition causing significant mortality and long term morbidity. Early detection of intracranial changes and its consequences will enhance timely intervention and better out come. Cranial sonography can be done to assess the abnormalities of brain in perinatal asphyxia. Objectives: The objective of this study was to evaluate usefulness of cranial sonography in perinatal asphyxia. Methods: This was an observational study conducted from March 2014 to February 2015 at department of radiology and imaging, Enam Medical College and Hospital. Total 100 neonates with perinatal asphyxia were included in this study. Cranial USG was done in all cases and sonographic abnormalities were evaluated. Result: 56 term (>37 weeks of gestation ) and 44preterm (<37 weeks of gestation ) newborn having birth asphyxia were taken as cases in this study. Common cranial sonographic findings of preterm babies were periventricular leukomalacia 29% (13), germinal matrix hemorrhage 14% (6), Intraventricular hemorrhage 11% (5) cerebral oedema 7% (3) and normal 39% (17). Common cranial USG findings in term babies were cerebral oedema 43% (24), intracerebral hemorrhage 5% (3), Focal cerebral infarct 4% (2), Intraventricular hemorrhage 2% (1) and normal 46% (26). Conclusion: This study found that transcranial sonography is useful to identify the abnormalities in brain of asphyxiated neonate and helps to predict the neurodevelopmental outcome. So proper management plan can be done. J MEDICINE January 2016; 17 (1) : 12-16